International Development and Research Capacities: Increasing Access to African Scholarly Publishing - Metcalfe, Amy Scott; Esseh, Samuel; Willinsky, John (Canadian Journal of Higher Education, 2010)
This paper examines the evolving relationship between Canada and the African academic research community through the promotion of a concept known as Information and Communication Technology for Development (ICT4D) and with an eye to its implications for increasing the circulation of research through such means as open access (OA) publishing models. We analyze the programmatic discourse of Canada’s International Development Research Centre’s (IDRC) African research initiatives, and report on an IDRC research and development project assessing the means of increasing access to African scholarly journals through the use of open source software platforms and open access publishing and archiving models. Consistent with IDRC’s multi-year effort to contribute directly to university-based research capacities by investing in ICT infrastructure in Africa, our survey of African editors, librarians, and faculty from five African nations reveals a similar interest in developing those capacities, despite numerous challenges, through the use of online publishing systems and OA publishing models, which hold some promise of increasing access to research published in Africa.